Enhancing separation of fats, oils and greases (FOGs) from catering establishment wastewater - Barton, Paul (Cranfield University, 2012)
Removal of fats, oils and greases (FOG) from commercial food premises prior to discharge of wash waters into the sewer is critical in restricting blockage events. The FOG droplets that form are commonly removed in passive gravity separators. Enhanced separation through design modification, would allow a reduction in size required to achieve target removal. The aim of the project was to determine the feasibility of enhancing removal of FOGs in gravity separation devices and or in post treatment units. The thesis work examined the effect characteristics of oil droplet size and density had on FOG removal with a view to increasing droplet rise rates and hence separation. Examination of kitchen wastewater from a number of restaurants established that droplet sizes were typically in the mechanically emulsified oil size range, often with high zeta potential indicating electrostatic stabilisation of suspensions. Oil removal rates were examined using different oils typical of food preparations in laboratory scale experiments. Under a fixed energy input the different oils produced different droplet size distributions such that very different separation efficiencies were observed. The removal rates obtained allowed the prediction of oil removal from a sample in a given time when the median droplet size and density of the oil were known. For effective understanding of separator design and testing, droplet densities and sizes must be adequately measured and replicated. In addition, the light fuel oil used in the certification test produced very unstable suspensions, easily separable in the standard testing conditions, proving it a poor surrogate test material. Pre-formed droplets of sunflower oil were treated in a vertically aligned reaction chamber with an ultrasonic transducer fitted at the base. FOG removal, measured as HEM removal, was monitored as a function of power input, frequency, reactor size and residence time, the incoming flow entered counter currently to the ultrasonic wave propagation. The ultrasound treatment procedure removed 80% of oil from a suspension of droplets in the mechanically emulsified oil size range during the course of a 54 minute continuous experiment compared to 20-30% removal in the case of an equivalent separated without ultrasonic enhancement. The enhanced separation was found to be dependent on the power input and the reactor size. Application of ultrasound energy in modified grease separators to remove short-circuiting droplets would allow a reduction in overall size of units through reduced residence time requirement.